2022
DOI: 10.1186/s12920-022-01174-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into pancreatic adenocarcinoma pathogenesis using liquid association analysis

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy associated with a poor prognosis. High-throughput disease-related-gene expression data provide valuable information on gene interaction, which consequently lead to deeper insight about pathogenesis. The co-expression analysis is a common approach that is used to investigate gene interaction. However, such an approach solely is inadequate to reveal the complexity of the gene interaction. The three-way interaction model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Recent researches have also investigated LAMC2 as a valuable biomarker of cancer diagnosis. 36 37 Due to a limitation of the small sample size, we explored the expression of LAMC2 in various cancer types using (The Cancer Genome Atlas) TCGA database. The results showed that LAMC2 was upregulated in tumours and might be used as a biomarker for a variety of tumour types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent researches have also investigated LAMC2 as a valuable biomarker of cancer diagnosis. 36 37 Due to a limitation of the small sample size, we explored the expression of LAMC2 in various cancer types using (The Cancer Genome Atlas) TCGA database. The results showed that LAMC2 was upregulated in tumours and might be used as a biomarker for a variety of tumour types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have also investigated LAMC2 as a valuable biomarker of cancer diagnosis 36 37. Due to a limitation of the small sample size, we explored the expression of LAMC2 in various cancer types using (The Cancer Genome Atlas) TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, a pair of genes participating in a comparable biological pathway during a particular biological condition might lose their connection under a different biological circumstance. As a result, the degree and pattern of gene expression correlation between a pair of genes can be influenced by internal changes and cellular conditions 12 . Therefore, pairwise interaction analyses, in the classical sense, may be too simplistic to explain complex molecular relationships 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%